Cytological screening to detect subclinical anal human papillomavirus (HPV) infection in homosexual men attending genitourinary medicine clinic. - Haye, K R (1988)
Unselected homosexual men attending a department of genitourinary medicine were screened for human papilloma virus (HPV) infection using anal cytology. Satisfactory smears were obtained from 221 patients, and 73 showed cytological abnormality with warty atypia. Abnormal cytology was detected in 55 (31%) of 178 patients in whom there was no macroscopic evidence of anal or perianal warts, and anal cytology may therefore be valuable to detect patients with subclinical condylomatous lesions and may also serve to identify those who possibly have intraepithelial neoplasia.